Infrastructure, Competition Regimes and Air Transport Costs: Cross Country Evidence - Alejandro Micco; Tomas Serebrisky (Inter-American Development Bank, Research Department, 2004)
The relevance of transport costs has increased as liberalization continues to reduce artificial barriers to trade. Countries need to adopt policies to `get closer` to global markets. Can improvements in infrastructure and regulation reduce transport costs? Is it worthwhile to implement policies designed to increase competition in transport markets? Focusing on air transport, which has increased its share in US imports from 24 percent in 1990 to 35 percent in 2000, this paper quantifies the effects of infrastructure, regulatory quality and liberalization of air cargo markets on transport costs. During the 1990s, the US implemented a series of Open Skies agreements, which have provided a unique opportunity to assess the effect on prices of a change in the competition regime. We find that infrastructure, quality of regulation and competition matter. In our sample, an improvement in airport infrastructure from the 25th to 75th percentiles reduces air transport costs 15 percent. A similar improvement in the quality of regulation reduces air transport costs 14 percent. In addition, Open Skies agreements reduce air transport costs by 8 percent.
Keywords: 330; Verkehrsinfrastruktur; Luftfrachtverkehr; Transportkosten; Regulierung